Löwenstein-Buschke: Clinicopathologic Analysis of 78 Cases of Large and Giant Condyloma Acuminata of the Anus - Orhun CIG TASKIN (Türk Patoloji Dergisi, 2021)

(untitled)
Objective: The nature and clinicopathologic associations of Löwenstein-Buschke disease are unclear.